Effects of elevated temperature on the tropical soil bacterial diversity - Chin, Lai Mun; Wong, Clemente Michael Vui Ling (Penerbit Universiti Kebangsaan Malaysia, 2020)
Bacteria are important biological components of soil that play pivotal roles in improving soil quality and maintaining a balanced ecosystem. However, global climate change may have severe impacts on biodiversity and ecosystems including species loss and extinction of plants and animals, including microbes. Thus, it is crucial to determine how elevated temperature may alter soil bacterial diversity and composition. In this study, an in vitro simulated temperature rise experiment was carried out on soils from three sampling sites, referring to S1, S2, and S3 around Sabah, Malaysia. Soils were incubated at 25 °C (control) and 27 °C (simulated warming) with constant parameters in a growth chamber up to 16 months. Total DNA was extracted from microbes in the soil and used for PCR amplification targeting the V3-V4 region of the 16S rRNA gene. These amplicons were sequenced using the MiSeq platform (Illumina, USA). Raw DNA sequences were trimmed, merged, and aligned against the 16S rRNA sequences in the NCBI 16S database. The results showed that the analyzed soils were mainly dominated by Proteobacteria, Actinobacteria, Acidobacteria, and Verrucomicrobia. After 16 months of simulated warming, a net decrease of Proteobacteria, Acidobacteria, and Planctomycetes, and an increase of Actinobacteria and Chloroflexi were observed for all three soil samples, indicating that these phyla were highly affected by a temperature rise. At the genus level, Gaiella and Nocardioides exhibited a net increase while Bradyrhizobium, Mycobacterium, Tepidisphaera, and Paludibaculum demonstrated net decrease after 16 months of simulated warming. Knowledge on the changes of soil bacterial diversity patterns as a result of temperature elevation will contribute to select the best intervention strategy to overcome global warming issue in the future.